1984
DOI: 10.1002/ddr.430040212
|View full text |Cite
|
Sign up to set email alerts
|

The toxicology of the schistosomicidal agent oxamniquine

Abstract: Oxamniquine displayed low acute toxicity in mice, hamsters, and rabbits. In rats, however, oxamniquine was much more toxic, the female being 8-10 times more sensitive than the male; single doses elicited an idiosyncratic sex-linked hepatic necrosis and bile duct proliferation. Dogs given repeated oral doses of 20 or 30 mglkglday for 5 successive days every 4 weeks for 11 months showed neurological disturbances of short duration, which tended gradually to increase in severity from one dosage period to the next;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…223 The tumors are highly vascular so hemorrhage, thrombosis and necrosis may be seen. 241 In mice, they are generally much less common spontaneous lesions and less easily induced by administration of xenobiotics. They may be cytologically similar to normal pheochromocytes and arranged in characteristic cords and nests.…”
Section: Neoplasia Of Adrenal Medullamentioning
confidence: 99%
“…223 The tumors are highly vascular so hemorrhage, thrombosis and necrosis may be seen. 241 In mice, they are generally much less common spontaneous lesions and less easily induced by administration of xenobiotics. They may be cytologically similar to normal pheochromocytes and arranged in characteristic cords and nests.…”
Section: Neoplasia Of Adrenal Medullamentioning
confidence: 99%
“…Chronic studies showed no evidence of carcinogenic effects, and neither maternal toxicity nor teratogenicity were observed. Only weak embryotoxicity was detected after applying high oral doses . Studies of mutagenicity were mostly negative, occasionally weakly positive .…”
Section: Anthelmintic Drug Therapymentioning
confidence: 96%
“…Only weak embryotoxicity was detected after applyingh igh oral doses. [100] Studies of mutagenicityw ere mostly negative, occasionally weakly positive. [101][102][103] Side effects were often described to be mild and of short duration.N ausea, dizziness, drowsiness, headache, abdominald iscomfort, vomiting, and diarrhea were most commonly observed.…”
Section: Oxamniquinementioning
confidence: 99%